Desain Pembelajaran Pendidikan Agama Islam di Era Digital - Aszmi Farida; Indah Fatiha; Gusmaneli Gusmaneli (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2025)
The development of digital technology has a significant impact on various aspects of life, including education. Islamic Religious Education (PAI) as one of the main components in shaping learners' character and morals must also adapt to technological advances to remain relevant and effective. This article discusses the design of innovative PAI learning in the digital era, identifying the main challenges faced, as well as implementing solutions to improve learners' engagement and understanding in learning. This study uses a descriptive method with a literature approach to explore the use of technology in PAI learning. The study found that digital-based PAI learning design requires careful planning, active involvement of teachers, and collaboration between school and family to achieve optimal results. The results of this study are expected to serve as a guide for PAI educators in presenting relevant, interactive, and inspiring learning in the digital era.